How do you solve -67=-4n+3(1+6n) using the distributive property?

1 Answer
Jun 13, 2017

n = -5

Explanation:

-67 = -4n + 3(1 + 6n)

-67 = -4n + 3 + 18n

-67 color(red)(-3) = -4n color(red)(cancel(color(black)(+ 3) -3)) + 18n

-70 = -4n + 18n

-70 = 14n

-70/14 = (color(red)(cancel(color(black)(14)))n)/color(red)(cancel(14))

n = -70/14

color(blue)(n = -5

Now we can substitute n for -5 to prove our answer.

-67 = -4 xx -5 + 3(1 + 6 xx -5)

-67 = -4 xx -5 + 3(1 + -30)

-67 = -4 xx -5 + 3 xx -29

-67 = 20 + 3 xx -29

-67 = 20 + -87

-67 = -67